2018
DOI: 10.1186/s12933-018-0701-4
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide suppresses non-esterified free fatty acids and soluble vascular cell adhesion molecule-1 compared with metformin in patients with recent-onset type 2 diabetes

Abstract: BackgroundIt has been suggested that liraglutide could have an impact on glucose and lipid metabolism disorder and adhesion molecule activation, which may play important roles in the vascular damage of diabetes. In this study, we examined the effects of liraglutide versus metformin on non-esterified free fatty acids, beta-cell insulin secretion, and adhesion molecule levels in patients with recent-onset type 2 diabetes mellitus.MethodsIn this study, 60 patients newly diagnosed with type 2 diabetes mellitus (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Further, db/db mice fed with high fat diet improved hepatic lipid accumulation by promoting reversal of cholesterol transport [40]. In our model of metabolic syndrome, Vcam-1 mRNA expression showed a strong trend to be reduced by LIRA in the kidney [21] but not in the myocardium [13]. On the other hand, markers of macrophage infiltration (CD68 protein expression and CD+ cell density in sections) suggest that LIRA greatly suppressed macrophage infiltration in both the heart and kidney in our studies.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Further, db/db mice fed with high fat diet improved hepatic lipid accumulation by promoting reversal of cholesterol transport [40]. In our model of metabolic syndrome, Vcam-1 mRNA expression showed a strong trend to be reduced by LIRA in the kidney [21] but not in the myocardium [13]. On the other hand, markers of macrophage infiltration (CD68 protein expression and CD+ cell density in sections) suggest that LIRA greatly suppressed macrophage infiltration in both the heart and kidney in our studies.…”
Section: Discussionmentioning
confidence: 60%
“…LIRA treatment shown greater reductions in HbA1c in patients with cardiovascular events compared with placebo [12]. In addition, LIRA administration was more effective than metformin in suppressing vascular cell adhesion molecule (VCAM)-1 levels and reducing non-esterified free fatty acids recent-onset T2DM [13]. Indeed, previous studies have reported that GLP-1 agonist treatment has anti-inflammatory effects on peripheral vascular endothelial cells by increasing NO production and inhibiting cellular oxidative stress and apoptosis in diabetic animal models [14][15][16].…”
mentioning
confidence: 99%
“…Reduction in arterial stiffness, LV myocardial strain, twisting and untwisting, N-terminal pro-brain natriuretic peptide, and oxidative stress with liraglutide could offer myocardial protection and prevention of diabetic heart disease [55]. Moreover, liraglutide reduces postprandial non-esterified free fatty acids and suppresses soluble vascular cell adhesion molecule-1 compared to metformin [56]. It protects against acute liver injury in the mouse [57].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated in this study that liraglutide and metformin treatment significantly reduced the expression of urinary 8-OH-DG and 8-iso-PGF 2α .than those of baseline. At the same time, we also demonstrated that liraglutide treatment inhibited the expression of sVCAM-1 and hs-CRP [25]. 8-Hydroxy-2′-deoxyguanosine (8-OHdG), produced by oxidation of the nucleoside deoxyguanosine and subsequently excreted directly into urine, has been considered as a sensitive marker for oxidative DNA damage [26].…”
Section: Discussionmentioning
confidence: 99%